1991
DOI: 10.1111/j.1365-2818.1991.tb03174.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital three‐dimensional visualization of cellular organelles studied by medium‐ and high‐voltage electron microscopy

Abstract: K E Y w ORDS. Medium-and high-voltage EM, nucleolus, Ag-NOR, bas-relief. S U M M A R YTilted thick sections (one-half to several micrometres) of biological specimens observed with medium-to high-voltage electron microscopes are extremely useful for the study of the three-dimensional (3-D) structure of organelles.If high resolution in 3-D visualization and 3-D reconstruction is needed, many images corresponding to various angles of rotation and tilt must be recorded. This necessitates very time-consuming work-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the literature, it is generally admitted that the goblet cells shape differs from the serous cells in that their secretory granules are electron-lucent, more or less confluent. For the goblet cells of the intestine and sublingual glands of the rat [3] it has been reported that the respiratory mucus is discharged from the mucous cells through gaps formed by the rupture of their apical plasma membrane. The fact is that in electron-dense surface secretory cells (generally called serous cells), the membrane of their secretory granules often appears to be retained without any fusion [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it is generally admitted that the goblet cells shape differs from the serous cells in that their secretory granules are electron-lucent, more or less confluent. For the goblet cells of the intestine and sublingual glands of the rat [3] it has been reported that the respiratory mucus is discharged from the mucous cells through gaps formed by the rupture of their apical plasma membrane. The fact is that in electron-dense surface secretory cells (generally called serous cells), the membrane of their secretory granules often appears to be retained without any fusion [19].…”
Section: Discussionmentioning
confidence: 99%
“…The method of bas-relief micrography has been reported to be particularly suitable to enhance structures with blurred or smeared boundaries like limiting membranes [8]. The improvement of this method [3] gives a standardized 3-D computerized vision of the organelles of the epithelial ciliated and secretory cells by the superimposition of the light and shadows of the added highlights. The main advantage is that this 3-D information obtained from the stereopair can be transferred into a single image easily readable.…”
Section: Discussionmentioning
confidence: 99%
“…Stereology (Beorchia et al, 1991;Dustin et al, 1991;Furrer et al, 1995) was used to determine 3-D locations of features in the tilt pairs from which coordinates of nucleosome positions and internucleosomal distances and angles were derived. Where possible, x,y,z coordinates were determined for nucleosome centers and linker DNA entry-exit sites, and several points along each linker DNA and used to calculate the following parameters (see Fig.…”
Section: Image Analysismentioning
confidence: 99%
“…An aqueous environment is retained, and, for structures of the size scale of small oligonucleosomes, the complete 3-D conformation may be preserved. From tilt pairs of micrographs, stereology (Beorchia et al, 1991;Dustin et al, 1991), provides 3-D information concerning distances between consecutive nucleosomes, linker DNA trajectories, and the relative orientation of consecutive nucleosomes. We show here that cryoelectron microscopy provides greatly improved images of oligonucleosomes in solution, allowing the results of solution studies on saltinduced compaction to be correlated directly with changes in conformation.…”
mentioning
confidence: 99%